Comparison of the efficacy and safety of tacrolimus monotherapy and cyclophosphamide combined with glucocorticoid in the treatment of adult primary membranous nephropathy: protocol of a multicenter, randomized, controlled, open study - Shasha Chen; Song Ren; Amanda Y. Wang; Hieu Tran; Zheng Li; Xiaoyun Cheng; Manli Liu; Guisen Li; Li Wang; Daqing Hong (Trials, 2020)
Abstract Background Idiopathic membranous nephropathy (IMN) remains the leading cause of adult nephrotic syndrome. Immunosuppressive therapy with cyclophosphamide (CTX) is often successful in reducing proteinuria, but its use is associated with severe side effects. Tacrolimus (TAC) is effective in achieving complete remission (CR) in patients with IMN. However, whether it is as effective as CTX in inducing and maintaining complete or partial remission in these patients is unknown. This trial aims to test TAC monotherapy for its non-inferiority to CTX in inducing long-term remission of proteinuria. Methods Patients with biopsy-proven IMN with nephrotic syndrome will be randomized into a 12-month treatment period with oral TAC of 0.05–0.1 mg/kg/day for 6 months or with CTX + glucocorticoid. The efficacy of the treatment will be assessed by the remission status (based on changes in proteinuria) and relapse rate. Discussion This study will test whether treatment with TAC monotherapy is superior to CTX with glucocorticoid in inducing long-term remission of proteinuria in patients with adult IMN. The role of serum anti-PLA2R antibodies in the early assessment of the response to therapy using different therapeutic regimens will also be clarified. Trial registration ClinicalTrials.gov ChiCTR1800016140. Registered 12 June 2017. http://www.chictr.org.cn.